The Influence of Grit And Self Compassion on Resilience in Pandemic - Ade Ubaidah (Journal on Education, 2023)
If students do not have good resilience, it will be difficult to follow the learning process and live a daily life that is felt to be unsatisfactory. Resilience does not only refer to negative mental health, but also refers to how an individual is able to develop their potential and abilities optimally, as individuals who function both physically, emotionally and psychologically. Therefore, this study aims to determine the effect of self compassion and grit on student resilience during a pandemic. The method used is descriptive quantitative. The results concluded that the variables of grit and self-compassion affect either partially or simultaneously the resilience of students during Covid 19 pandemic.